Preparation method of water-soluble polymer used as shale encapsulating agent for drilling fluid
By reacting a water-soluble monoethylenically unsaturated monomer with a free radical initiator in an aqueous solution and drying it to obtain a polymer, the problem of free radical polymerization in aqueous solutions in the prior art is solved, and efficient and simplified polymerization is achieved. Polymerization process to prepare high molecular weight water-soluble polymers suitable for oil drilling.
Patent Information
- Application Number
- CN202380046346.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-14
- Filing Date
- 2023-06-12
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to successfully perform radical polymerization in aqueous solutions, and traditional reverse phase suspension or emulsion polymerization methods require the use of organic solvents and surfactants, which are complex and costly.
By continuously measured the water -soluble monoclonal unsaturated monomer in the aqueous solution containing free radicals, and obtained polymers under dry conditions to achieve free radical aggregation in the aqueous solution to avoid using organic solvents. And surfactant.
Successfully prepared a water -soluble polymer in the form of powder in the form of a high molecular weight, and the process is simplified to avoid unnecessary steps and costs. The obtained polymers are suitable for the shale packagers and inhibitors in the petroleum drilling field.
Smart Images

Figure BDA0005181790960000301 
Figure BDA0005181790960000311 
Figure HDA0005181790970000011
Abstract
Description
[0001] The present invention relates to a process for producing water-soluble polymers in powder form, which contain at least two different ethylenically unsaturated monomers, namely an ethylenically unsaturated monomer containing at least one OH group or an oxyalkylene group, and another monomer, by metering these monomers into an aqueous solution containing at least one free-radical initiator and drying the polymer obtained. The invention also relates to the use of these polymers in the field of oil drilling, in particular as shale encapsulants and / or shale inhibitors.
[0002] The introduction of hydroxyl functional groups into water-soluble polymers, such as polymers containing acrylic acid and / or arylamide, provides interesting properties for certain industrial sectors. Examples include cationic anti-precipitation agents (particularly in brines used in gas and oil production operations), surface agents on paper coatings or clays, and shale inhibitors or shale encapsulants in the oil drilling field.
[0003] During the process of drilling a wellbore, the drilling fluid transports the cuttings produced by the drilling to the surface, where the cuttings are separated from the drilling fluid and then the drilling fluid is reinjected into the wellbore. The formations drilled through typically include shales and clays. Clays and shales react with the water phase of the drilling fluid, thereby promoting viscosity, increasing swelling and causing shedding. Therefore, it is known in the art to add shale and clay stabilizers to the drilling fluid. Such stabilizers adhere to the cuttings and the wellbore wall.
[0004] This encapsulation can effectively seal their surfaces and inhibit their reaction with drilling fluids, thereby minimizing adhesion, swelling and shedding, and improving the stability of the borehole.
[0005] Unfortunately, the introduction of hydroxyl functional groups brings with it many difficulties, especially if high molecular weights are desired. Hydroxyl functional groups may undergo migration phenomena and thus eventually cause crosslinking problems. For example, carboxyl functional groups present in acrylic acid may lead to unwanted esterification reactions. Whether occurring during or after polymerization, such esterifications lead to the formation of insoluble products and are therefore unsuitable for use.
[0006] Polymers in the form of powders or beads are increasingly sought and desired at the industrial level because they are easy to transport and have a very high concentration of active substances. In addition, they have a much longer shelf life relative to polymers in the form of liquids or emulsions and have the advantage of not needing to contain additional protective agents (such as biocides).
[0007] Document JP-1981-161413 describes a process for the inverse suspension synthesis of nonlinear polymers containing hydroxyalkyl monomers, wherein the crosslinking effect of alcohol functional groups is utilized to obtain self-crosslinking and thus water-swellable polymers.
[0008] US2017 / 0204210 A1 discloses water-soluble polymers in the form of beads or powders, which are obtained by reverse suspension or emulsion polymerization in the presence of a transfer agent. They can be used as shale inhibitors in drilling processes. These polymers contain at least two different ethylenically unsaturated monomers, i.e., ethylenically unsaturated monomers containing OH- groups, such as hydroxypropyl acrylate, and another monomer, in particular acrylic acid. The amount of OH-containing monomers is limited to less than 20 mol%. At the end of the reaction, water is evaporated and the polymer beads can be separated from the organic phase. The document includes comparative examples in which the synthesis is performed by solution polymerization followed by drying of the aqueous solution. A mixture of acrylic acid, hydroxypropyl acrylate, water and NaOH is added to a reactor, after which an initiator and a transfer agent are added and the mixture is polymerized. Due to crosslinking, the polymer powder obtained contains an amount of insoluble matter greater than 2 wt.%.
[0009] However, inverse suspension polymerization and inverse emulsion polymerization require the use of organic solvents. It is desirable to avoid the use of organic solvents. In addition, this method requires surfactants and emulsion stabilizers. These compounds are expensive and may have a negative impact on the final application of the product. In addition, the above method involves many different steps. The method starts with the generation of the emulsion, followed by the polymerization itself. The polymer beads then need to be filtered out and dried from the residual water and solvent. Finally, there is a distillation step to recycle the solvent. All these steps make the method tedious, expensive and not very robust.
[0010] For these reasons, free radical polymerization in aqueous solution is highly desirable. However, no successful methods for conducting such free radical polymerization in aqueous solution are disclosed in the prior art. As shown in Comparative Examples CE-1 and CE-2 of US 2017 / 0204210A1 and Comparative Example 2 of the present invention, polymerization cannot be successfully carried out by simply mixing monomers and free radical initiators in a reaction vessel.
[0011] WO 2011 / 118728, CN 113 072 666, CN 111 072 666, JP H03 197519A, US 2013 / 289171 and EP 0344589 disclose methods for preparing aqueous solutions of water-soluble polymers. However, the obtained water-soluble polymers are not dried to prepare powder forms. And none of these prior art documents disclose the uses and advantages of water-soluble copolymers in powder form in the field of oil drilling, in particular as shale encapsulants and / or shale inhibitors.
[0012] It is therefore an object of the present invention to provide a process for preparing a water-soluble copolymer in powder form by free-radical polymerization in aqueous solution, the water-soluble copolymer comprising at least two different ethylenically unsaturated monomers, namely an ethylenically unsaturated monomer comprising an OH group or an oxyalkylene group, and a further monomer.
[0013] The Applicant has found that the continuous metering of monomers over time into an aqueous solution comprising at least one free-radical initiator and the subsequent drying of the polymer obtained make it possible to obtain water-soluble polymers having a high molecular weight in powder form.
[0014] The present invention therefore relates to a process for preparing a water-soluble polymer in powder form by free-radical polymerization of at least two water-soluble monoethylenically unsaturated monomers (A) and (B), wherein
[0015] Monomer (A) has the formula H 2 C=C(R 1 )-CO-XR 2 , where R 1 is H or CH 3 , X is O or NR 3 , where R 3 is H or CH 3 , and R 2 is a hydrocarbon radical containing at least one OH side group or having the formula –(CH 2 CH(R 4 )-O) n R 5 A group in which R 4 and R 5 are independently H or CH 3 , and n is selected from 1 to 20, and wherein the amount of monomer (A) is 0.1 to 30 mol% relative to the total amount of all monomers, and
[0016] Monomer (B) is a monomer different from (A) and has the general formula H 2 C=C(R 1 )-R 6 , where R 1 has the meaning as defined above, and R 6 is a hydrophilic group, and the amount of monomer (B) is 70 to 99.9 mol% relative to the total amount of all monomers.
[0017] Characterized in that the method comprises at least the following steps
[0018] i) adding an aqueous base fluid to a container,
[0019] ii) adding at least one free radical initiator to a container and dissolving the free radical initiator in an aqueous base fluid,
[0020] iii) continuously metering the monomer into the container, and
[0021] iv) removing the obtained water-soluble polymer from the container and drying it,
[0022] And wherein the maximum temperature of the container is equal to or less than 100°C at any point during the process. Description of the drawings:
[0023] Figure 1 : GPC analysis results of Comparative Example 2.
[0024] Monomer to be used
[0025] For the process of the invention, at least two water-soluble monoethylenically unsaturated monomers (A) and (B) are used, wherein
[0026] Monomer (A) has the formula H 2 C=C(R 1 )-CO-XR 2 , where R 1 is H or CH 3 , X is O or NR 3 , where R 3 is H or CH 3 , and R 2 is a hydrocarbon radical containing at least one OH side group or having the formula –(CH 2 CH(R 4 )-O) n R 5 A group in which R 4 and R 5 are independently H or CH 3 , and n is selected from 1 to 20, and wherein the amount of monomer (A) is 0.1 to 30 mol% relative to the total amount of all monomers, and
[0027] Monomer (B) is a monomer different from (A) and has the general formula H 2 C=C(R 1 )-R 6 , where R 1 has the meaning as defined above, and R 6 is a hydrophilic group, and wherein the amount of the monomer (B) is 70 to 99.9 mol% relative to the total amount of all monomers.
[0028] In one embodiment, R 2 The group is a C 1 -C12 Hydrocarbyl, preferably C 1 -C 6 Hydrocarbyl, and most preferably C 1 -C 4 Hydrocarbon.
[0029] In one embodiment, at least one monomer (A) is selected from hydroxyalkyl (meth)acrylates,
[0030] Hydroxyalkyl (meth)acrylamides and amino alcohol (meth)acrylates, wherein the term "alkyl" is a straight chain alkyl group containing 1 to 12 carbon atoms, preferably 1 to 6 carbon atoms, most preferably 1 to 4 carbon atoms.
[0031] In further embodiments, at least one monomer (A) is a hydroxyalkyl (meth)acrylate selected from hydroxymethyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, such as 2,3-dihydroxypropyl methacrylate.
[0032] In another embodiment, at least one monomer (A) is a hydroxyalkyl (meth)acrylamide selected from the group consisting of hydroxymethyl (meth)acrylamide, hydroxyethyl (meth)acrylamide, hydroxypropyl (meth)acrylamide, and hydroxybutyl (meth)acrylamide.
[0033] In another embodiment, at least one monomer (A) is an amino alcohol (meth)acrylate, such as N-[tris(hydroxymethyl)aminomethane](meth)acrylamide.
[0034] In a preferred embodiment, at least one monomer (A) is hydroxypropyl (meth)acrylate.
[0035] In one embodiment, the water-soluble polymer comprises 0.1 to 30 mol%, preferably 5 to 25 mol%, most preferably 15 to 25 mol% of at least one monomer (A), relative to the total amount of all monomers.
[0036] In one embodiment, at least one monomer (B) may be selected from:
[0037] anionic monomers, preferably selected from acrylic acid, methacrylic acid, itaconic acid, maleic acid, 2-acrylamido-2-methylpropanesulfonic acid (ATBS), said monomers being in acid form, partially salified or fully salified;
[0038] • Nonionic monomers, preferably selected from acrylamide, methacrylamide, N,N'-dimethylacrylamide, N-vinylpyrrolidone, N-vinylformamide, methacrylates, diacetoneacrylamide and N-isopropylacrylamide.
[0039] In one embodiment, at least one of the monomers (B) is a cationic monomer. In a preferred embodiment, the amount of the cationic monomer is less than 10 mol% relative to the total amount of all monomers. Suitable cationic monomers (B) are monomers containing ammonium groups, in particular ammonium derivatives of N-(o-aminoalkyl) (meth) acrylamide or L-aminoalkyl (meth) acrylate.
[0040] In particular, the monomer (B) having an ammonium group may be a monomer having the general formula H 2 C=C(R 7 )-CO-NR 10 -R 8 -NR 9 3 + X - (I) and / or H 2 C=C(R 7 )-COO-R 8 -NR 9 3 + X - (II), wherein R 7 is H or methyl, R 8 Preferably, it is a straight chain C 1 -C 4 -alkylene, and R 10 Is H or C 1 -C 4 -alkyl, preferably H or methyl. The group R 9 Independently of each other, C 1 -C 4 -alkyl, preferably methyl, or having the general formula -R 11 -SO 3 H group, where R 11 Preferably a straight chain C 1 - to C 4 - alkylene or phenylene, provided that the substituent R 9 No more than one of the three substituents R is a substituent having a sulfonic acid group. 9 Particularly preferred are methyl groups, ie monomers having the group -N(CH 3 ) 3 + In the above formula, X - It is a monovalent anion, such as CI - .X -Of course, it is also possible to be the corresponding part of a polyvalent anion, although this is not preferred. Examples of suitable cationic monomers (B) of the general formula (I) or (II) include salts of 3-trimethylammoniumpropylacrylamide or 2-trimethylammoniumethyl(meth)acrylate, for example the corresponding chlorides, such as 3-trimethylammoniumpropylacrylamide chloride (DIMAPAQUAT) and 2-trimethylammoniumethylmethacrylate chloride (MADAME-QUAT).
[0041] In one embodiment of the present invention, monomer (B) is (meth)acrylic acid or a salt thereof.
[0042] In one embodiment, the water-soluble polymer comprises 70 to 99.9 mol%, preferably 75 to 95 mol%, most preferably 75 to 85 mol% of at least one monomer (B), relative to the total amount of all monomers.
[0043] In a preferred embodiment, the water-soluble polymer comprises 75-85 mol % of (meth)acrylic acid or a salt thereof and 15-25 mol % of a monomer (A) as defined previously.
[0044] In one embodiment of the present invention, the water-soluble polymer may further include additional monomers in addition to the monomers (A) and (B).
[0045] In another embodiment of the present invention, the water-soluble polymer contains only monomers (A) and (B).
[0046] Prepared water-soluble polymer
[0047] The water-soluble polymer prepared by the method of the present invention comprises the monomers as described above, in the amounts as described above, including the preferred embodiments.
[0048] The weight average molecular weight (M w ) is selected by the skilled person according to its intended use. For many applications, a high molecular weight is desired. In one embodiment, the molecular weight (M) of the water-soluble polymer is w ) is in the range of 500,000 to 1,500,000 g / mol, preferably in the range of 600,000 to 1,200,000 g / mol.
[0049] And the obtained water-soluble polymer contains an amount of insoluble matter less than 2 wt.%.
[0050] The prepared polymers were analyzed for molecular weight, viscosity, and the amount of insoluble matter as will be described below.
[0051] Method to be used
[0052] The present invention relates to a process for preparing a water-soluble polymer in powder form by free-radical polymerization of at least two water-soluble monoethylenically unsaturated monomers (A) and (B), wherein
[0053] Monomer (A) has the formula H 2 C=C(R 1 )-CO-XR 2 , where R 1 is H or CH 3 , X is O or NR 3 , where R 3 is H or CH 3 , and R 2 is a hydrocarbon radical containing at least one OH side group or having the formula –(CH 2 CH(R 4 )-O) n R 5 A group in which R 4 and R 5 are independently H or CH 3 , and n is selected from 1 to 20, and wherein the amount of monomer (A) is 0.1 to 30 mol% relative to the total amount of all monomers, and
[0054] Monomer (B) is a monomer different from (A) and has the general formula H 2 C=C(R 1 )-R 6 , where R 1 has the meaning as defined above, and R 6 is a hydrophilic group, and the amount of monomer (B) is 70 to 99.9 mol% relative to the total amount of all monomers.
[0055] Characterized in that the method comprises at least the following steps
[0056] i) adding an aqueous base fluid to a container,
[0057] ii) adding at least one free radical initiator to a container and dissolving the free radical initiator in an aqueous base fluid,
[0058] iii) continuously metering the monomer into the container, and
[0059] iv) removing the obtained water-soluble polymer from the container and drying it,
[0060] And wherein the maximum temperature of the container is equal to or less than 100°C at any point during the process.
[0061] As described above, the method for preparing a water-soluble polymer in powder form comprises at least steps i) to iv).
[0062] During step i), an aqueous base liquid is added to the reaction vessel. In one embodiment, the vessel is then heated before carrying out step ii). In a further embodiment, the vessel is heated to a temperature between 45°C and 85°C, preferably between 55°C and 85°C, more preferably between 55°C and 70°C.
[0063] The term "aqueous base fluid" as used throughout the present invention is intended to encompass any solution comprising water. The aqueous base fluid may additionally comprise an organic solvent miscible with water. In one embodiment, the aqueous base fluid comprises at least 50 wt.%, preferably at least 80 wt.%, most preferably at least 95 wt.% of water relative to the total amount of all components of the aqueous base fluid. In a further embodiment of the present invention, the aqueous base fluid is only water.
[0064] During step ii), at least one free radical initiator is added to the reaction vessel and dissolved in the aqueous base fluid. In one embodiment, the free radical initiator is dissolved in water for 10 h. 1 / 2 The temperature is 20°C to 70°C, preferably 40°C to 60°C. In another embodiment, the free radical initiator is selected from 2,2'-[azobis(1-methylethylidene)]bis[4,5-dihydro-1H-imidazole dihydrochloride (Wako VA-044, whose 10h t1 / 2 temperature in water is 44°C;); 2,2'-azobis[2-methylpropionamidine] dihydrochloride (WakoV50, whose 10h t1 / 2 temperature in water is 56°C) and sodium peroxodisulfate. In a preferred embodiment, the free radical initiator is 2,2'-[azobis(1-methylethylidene)]bis[4,5-dihydro-1H-imidazole dihydrochloride (Wako VA-044).
[0065] During step iii), the monomers are metered continuously into the reaction vessel. In one embodiment, the monomers in step iii) are metered into the vessel via a dropping funnel, via a pump (such as a peristaltic pump) or via any other metering means known to the skilled person.
[0066] In one embodiment, the monomer is continuously metered into the reaction vessel over a period of 15 to 120 min, preferably 30 to 90 min, and more preferably 45 to 75 min. In one embodiment, the metering rate of the monomer may be controlled so as not to exceed the desired upper limit of the vessel temperature.
[0067] In one embodiment, the monomers are metered into the reaction vessel as a monomer mixture. Alternatively, in another embodiment, the monomers are metered into the reaction vessel individually. When monomers are added individually, they can be metered at the same metering rate or at different metering rates.
[0068] In another embodiment, up to 30 wt. % of the monomers used in the process relative to the total amount of monomers added to the vessel during the process is added to the reaction vessel prior to the free radical initiator.
[0069] In one embodiment, the vessel is cooled after the reaction between the monomer and the free radical initiator begins in order to control the desired upper limit of the vessel temperature. In one embodiment, cooling is performed by using a cooling jacket or a recirculating chiller or adding cold water to the vessel, or any other cooling means known to the skilled person.
[0070] In one embodiment, when at least one of the monomers is a salt of (meth)acrylic acid, the salt may be prepared in advance and then added to the reaction vessel. Alternatively, the reactants may be added to the reaction vessel separately. In a preferred embodiment, when at least one of the monomers is sodium acrylate, sodium acrylate may be prepared in advance and then added to the reaction vessel. Alternatively, acrylic acid and NaOH may be added to the container separately.
[0071] In one embodiment, after the monomer metering is complete, the reaction vessel is stirred at a temperature between 45°C and 85°C, preferably between 55°C and 85°C, more preferably between 55°C and 70°C for 30 min to 3 h.
[0072] In one embodiment, after the monomer metering is complete, an additional amount of free radical initiator is added to the vessel.
[0073] In one embodiment, the final polymer concentration in the reaction vessel before step iv) is in the range of 18 to 35 wt.%, preferably 18 to 30 wt.%.
[0074] In one embodiment, the temperature of the vessel is maintained at or below 100° C. by cooling, such as using a cooling jacket or a recirculating cooler or adding cold water to the vessel. And in a preferred embodiment, the maximum temperature of the vessel is at or below 90° C., preferably at or below 85° C., at any point during the process.
[0075] During step iv), the obtained water-soluble polymer is removed from the container and dried. In one embodiment, a drum dryer is used to dry the polymer. In another embodiment, the polymer is dried by a drum dryer at a temperature of 110° C. to 180° C. for 30 s to 5 min.
[0076] An additional advantage of the process of the invention compared to the prior art (eg the process exemplified in EP 3 177 654 B1) is that no transfer agent is required.
[0077] Other embodiments
[0078] In addition, in another embodiment, the present invention also relates to the use of the water-soluble polymer described by the above method in the field of oil drilling. In a preferred embodiment, the present invention relates to the use of the water-soluble polymer as a shale encapsulant and / or shale inhibitor in oil drilling operations.
[0079] For oil drilling operations, a powder comprising a water-soluble polymer may be dissolved in an aqueous liquid to prepare a wellbore treatment fluid. The aqueous base fluid may include fresh water or brine, optionally selected from seawater, saturated NaCl, and KCl. Preferably, the aqueous base fluid is not a calcium brine having a calcium content greater than 500 mg / L. The dilution rate may vary and should be based on the consumption rate of the shale encapsulant or shale inhibitor.
[0080] The concentration of water-soluble polymers in wellbore treatment fluids used in oil drilling operations can be between 1.4 and 11.4 kg / m 3 in the range between.
[0081] In addition, the powder containing the water-soluble polymer can be pre-dissolved to 11.4 to 14.2 kg / m prior to final dilution into the wellbore treatment fluid. 3 concentration.
[0082] In a preferred embodiment, the pH of the wellbore treatment fluid containing the water-soluble polymer is maintained below 10.
[0083] In another embodiment, the present invention relates to the use of the water-soluble polymer described by the above method in the fields of gas recovery (or gas extraction), oil recovery (crude oil extraction), papermaking, water treatment, or agriculture.
[0084] The invention is further illustrated by the following examples, which are analyzed as indicated herein:
[0085] Analysis of polymers
[0086] Gel Permeation Chromatography
[0087] The molecular weight distribution of the polymer samples was analyzed by gel permeation chromatography. A combination of three different columns (Shodex OHpak SB-G, Shodex SB-807HQ and Shodex SB-806HQ) was used. The eluent was a mixture of 0.05 M ammonium formate / methanol (80:20 Vol%) at a flow rate of 0.5 ml / min. Detection was performed by refractive index.
[0088] Analysis of residual monomer content
[0089] The amount of unpolymerized monomers was analyzed by HPLC using a Nucleosil C18 column from Machery Nagel. The HPLC was performed using methanol and 0.05 M KH 2 PO 4 A mixture of aqueous solutions was used as eluent.
[0090] Viscosity measurement
[0091] For viscosity measurement, an aqueous solution containing 5 wt.% of the polymer was prepared, and the viscosity was measured by a Brookfield HV viscometer at 25°C and a rotation speed of 20 rpm using a No. 1 spindle.
[0092] The amount of insoluble matter
[0093] The insoluble content of polymer powder was measured according to the following procedure:
[0094] 1. Pour 1 g of polymer powder into 200 ml of tap water and stir for 2 h.
[0095] 2. Filter the polymer solution through a 200 μm stainless steel mesh.
[0096] 3. After the filter is drained, rinse it with water.
[0097] 4. If less than 30 spots remain on the filter, the insoluble content is assessed as <1 wt.%. If the sieve is covered but the solution is filtered, the insoluble content is reported as <2 wt.%. If the solution cannot be filtered through the sieve, the sieve is dried and weighed. The insoluble content is calculated from the difference between the initial weight of the filter and the weight after filtration and drying.
[0098] Examples
[0099] Comparative Example 1: Bead Polymerization
[0100] Copolymer of sodium acrylate (79.5 mol %) and hydroxypropyl acrylate (20.5 mol %) obtained by bead polymerization.
[0101] For comparative purposes, a commercially available copolymer prepared by a bead polymerization process was used.
[0102] The viscosity of the product was 140 mPas (measured in 5 wt.% aqueous solution by Brookfield HV viscometer at 25°C and 20 rpm with spindle 1). Residual acrylic acid was determined by HPLC to be 0.11 wt.%, and residual HPA to be 0.01 wt.%. Molecular weight (M) was measured by GPC. w ) was 823,000 Da. The insoluble content was determined to be <1 wt.%.
[0103] Comparative Example 2: Solution Polymerization
[0104] A copolymer of sodium acrylate (79.5 mol %) and hydroxypropyl acrylate (20.5 mol %) obtained by solution polymerization.
[0105] 640g of tap water was loaded into a 2L round-bottomed flask equipped with a condenser, a pH electrode, a stainless steel stirrer and a thermometer. Next, 89.6g of acrylic acid was added and then carefully neutralized with 193g of a 20wt.% NaOH solution under cooling. The temperature was maintained below 25°C during the neutralization process. Finally, 41.6g of hydroxypropyl acrylate (HPA) was added. The monomer solution was then purged with nitrogen and heated to a starting temperature of 45°C. Once the starting temperature was reached, 2.6g of azo initiator 2,2'-azobis[2-methylpropionamidine] dihydrochloride (Wako V50; 8wt.% aqueous solution), 4g of sodium peroxodisulfate (20wt.% aqueous solution) and 0.65g of sodium sulfite (20wt.% aqueous solution) were added to initiate polymerization. An exothermic reaction was observed immediately, and the temperature rose to 61°C in about 30min.
[0106] At this point, a sample was taken out and analyzed for unreacted monomers by HPLC, and the molecular weight of the polymer obtained was analyzed by gel permeation chromatography (GPC). The sample still contained a large amount of unpolymerized acrylic acid (3.66 wt.%), while the share of unpolymerized HPA was already quite low (0.14 wt.%). These findings indicate that the reactivity of HPA is higher than that of acrylic acid. Initially, the amount of acrylic acid in the monomer solution was 9.3 wt.%, and HPA was 4.3 wt.%, i.e., during the first 30 min of the polymerization reaction, the initial ratio of acrylic acid / HPA changed from about 2:1 to 26:1.
[0107] After the exothermic reaction was over, the temperature was raised to 75° C. and maintained at this temperature for 2 h. At the end of the reaction, the polymer solution was analyzed again for unreacted monomers by HPLC and for molecular weight by gel permeation chromatography. The residual amount of acrylic acid was found to be 0.52 wt.% and the residual amount of HPA was 0 wt.%. The active substance content of the final polymer solution was 13.5 wt.%, and the viscosity at 20° C. was 24 000 mPas.
[0108] The results of GPC analysis are shown in Figure 1 It shows a single peak for the first sample ( Figure 1 However, during further polymerization at 75 °C, a second peak with lower molecular weight appeared ( Figure 1 Taking into account the results from the monomer analysis, it can be concluded that this second peak can be assigned to the homopolymer of poly(acrylic acid), i.e. the final product consists of a mixture of poly(acrylic acid) and HPA-acrylic acid copolymer.
[0109] The solution was dried using a laboratory drum dryer (Merto Drum L, manufacturer Deutsche Vakuum Apparate, Holland Merten GmbH) at a temperature of 170° C. and a rotation speed of 1 rpm.
[0110] The obtained powder had a viscosity of 4050 mPas (measured by Brookfield HV viscometer at 25° C. and 20 rpm with spindle No. 1 in a 5 wt. % aqueous solution). The molecular weight (M w ) was 1,900,000 Da. For this polymer, an insoluble content of <2 wt.% was determined.
[0111] In summary, it was shown that homogeneous copolymers of acrylic acid and HPA could not be obtained by the above solution polymerization method due to the different reactivities of the monomers.
[0112] Example 1 of the present invention
[0113] A copolymer of sodium acrylate (79.5 mol %) and hydroxypropyl acrylate (20.5 mol %) prepared by the process according to the invention.
[0114] Preparation of sodium acrylate solution (39.6wt.% sodium acrylate):
[0115] 760 g of 20% aqueous NaOH solution was placed in a 2 L reaction vessel with a cooling jacket. A dropping funnel containing 360 g of acrylic acid was connected to the vessel and the acid was carefully dripped into the NaOH solution over 120 min. The temperature was kept below 25°C. The final pH was measured to be 5.7.
[0116] Polymer Synthesis:
[0117] 500 g of water was placed in a 2 L reaction vessel equipped with a dropping funnel, a stainless steel stirrer, a pH controller and a thermometer. The liquid was heated to 55° C. under nitrogen purge and stirring. At this temperature, 0.21 g of Wako V50 and 0.8 g of sodium peroxodisulfate were added and dissolved for 5 min.
[0118] Next, a mixture of 275 g of the sodium acrylate solution prepared above and 41.6 g of HPA was added via a dropping funnel within 35 min. A temperature increase of up to 63° C. was observed. The reaction mixture was stirred at 60° C. for a further 2 h.
[0119] The final polymer solution had a viscosity of 31 000 mPas (20° C., Brookfield HV 20 rpm) and a solids content of 18.4 wt.%. The pH was measured to be 5.7.
[0120] The solution was dried using a laboratory drum dryer (Merto Drum L, manufacturer Deutsche Vakuum Apparate, Holland Merten GmbH) at a temperature of 170° C. and a rotation speed of 1 rpm.
[0121] The resulting powder had a viscosity of 820 mPas (5 wt.% aqueous solution). The residual acrylic acid was determined by HPLC to be 0.38 wt.%, and the residual HPA to be 0 wt.%. The molecular weight (M) was measured by GPC. w ) was 1,191,000 Da. The insoluble content was determined to be <2 wt.%.
[0122] Example 2 of the present invention
[0123] A copolymer of sodium acrylate (79.5 mol %) and hydroxypropyl acrylate (20.5 mol %) prepared by the process according to the invention.
[0124] In the following examples, monomer addition was slower.
[0125] 500 g of water was placed in a 2 L reaction vessel equipped with a dropping funnel, a stainless steel stirrer, a pH controller and a thermometer. The liquid was heated to 57° C. under nitrogen purge and stirring. At this temperature, 0.21 g of azo initiator 2,2'-azobis[2-methylpropionamidine] dihydrochloride (Wako V50) and 0.8 g of sodium peroxodisulfate were added and dissolved for 5 min.
[0126] Next, a mixture of 275 g of the sodium acrylate solution prepared as described in Example 1 and 41.6 g of HPA was added via a dropping funnel within 60 min. A temperature increase was observed up to 62° C. The reaction mixture was stirred at 60° C. for a further 2 h.
[0127] The final polymer solution had a viscosity of 15 000 mPas (20° C.) and a solids content of 18.2 wt. %. The pH was measured to be 5.7.
[0128] The solution was dried using a laboratory drum dryer (Merto Drum L, manufacturer Deutsche Vakuum Apparate, Holland Merten GmbH) at a temperature of 170° C. and a rotation speed of 1 rpm. The viscosity of a 5 wt.% aqueous solution of the resulting powder was determined to be 230 mPas. Residual acrylic acid was determined by HPLC to be 0.32 wt.%, and residual HPA to be 0 wt.%. The molecular weight (M) was measured by GPC. w ) was 834,000 Da. The insoluble content was determined to be <2 wt.%.
[0129] Example 3 of the present invention
[0130] A copolymer of sodium acrylate (79.5 mol %) and hydroxypropyl acrylate (20.5 mol %) prepared by the process according to the invention.
[0131] Preparation of monomer solution (39.1 wt. %):
[0132] 570 g of a 20 wt.% aqueous NaOH solution was placed in a 4 L reaction vessel with a cooling jacket. A dropping funnel containing 270 g of acrylic acid was connected to the vessel and the acid was carefully dripped into the NaOH solution over 120 min. The temperature was kept below 25° C. Finally, 126 g of HPA was added and the monomer solution was purged with nitrogen.
[0133] Polymer Synthesis:
[0134] 780 g of water was placed in a 4 L reaction vessel equipped with a dropping funnel, a stainless steel stirrer, a pH controller and a thermometer. The liquid was heated to 53 ° C under nitrogen purge and stirring. At this temperature, 0.6 g of azo initiator 2,2'-azobis[2-methylpropionamidine] dihydrochloride (Wako V50) and 2.5 g of sodium peroxodisulfate were added and dissolved for 5 min.
[0135] Next, the monomer solution as described above was added via a dropping funnel within 90 min, keeping the temperature rising to a maximum of 65° C. The reaction mixture was stirred at 60° C. for a further 60 min.
[0136] The final polymer solution had a viscosity of 9 000 mPas (50° C.) and a solids content of 22.8 wt. %. The pH was measured to be 6.1.
[0137] The solution was dried using a laboratory drum dryer (Merto Drum L, manufacturer Deutsche Vakuum Apparate, Holland Merten GmbH) at a temperature of 170° C. and a rotation speed of 1 rpm. The viscosity of a 5 wt.% aqueous solution of the resulting powder was determined to be 300 mPas. Residual acrylic acid was determined by HPLC to be 0.12 wt.%, and residual HPA to be 0.01 wt.%. Molecular weight (M) was measured by GPC. w ) was 701,000 Da. The insoluble content was determined to be <2 wt.%.
[0138] Example 4 of the present invention
[0139] A copolymer of sodium acrylate (85 mol %) and hydroxypropyl acrylate (15 mol %) prepared by the process according to the present invention.
[0140] Preparation of monomer solution:
[0141] 660 g of tap water and 230 g of a 50 wt.% aqueous NaOH solution were placed in a 2 L reaction vessel with a cooling jacket. A dropping funnel with 270 g of acrylic acid was connected to the vessel and the acid was carefully dripped into the NaOH solution over 120 min. The temperature was kept below 25° C. Finally, 94.5 g of HPA was added and the monomer solution was purged with nitrogen.
[0142] Polymer Synthesis:
[0143] 500g of water was placed in a 2L reaction vessel equipped with a dropping funnel, a stainless steel stirrer, a pH controller and a thermometer. The liquid was heated to 55°C under nitrogen purge and stirring. At this temperature, 0.6g of azo initiator 2,2'-azobis[2-methylpropionamidine] dihydrochloride (Wako V50) dissolved in 5g of water and 2.5g of sodium peroxodisulfate dissolved in 5g of water were added. Next, the monomer solution was added through a dropping funnel within 90min, keeping the temperature rising to a maximum of 65°C. The reaction mixture was stirred at 60°C for another 60min.
[0144] The final polymer solution had a viscosity of 114 000 mPas (20° C.) and a solids content of 23.0 wt. %. The pH was measured to be 4.9.
[0145] The solution was dried using a laboratory drum dryer (Merto Drum L, manufacturer Deutsche Vakuum Apparate, Holland Merten GmbH) at a temperature of 170° C. and a rotation speed of 1 rpm. The viscosity of a 5 wt.% aqueous solution of the resulting powder was determined to be 600 mPas. Residual acrylic acid was determined by HPLC to be 0.12 wt.%, and residual HPA to be 0.01 wt.%. Molecular weight (M) was measured by GPC. w ) was 1,116,000 Da. The insoluble content was determined to be <1 wt.%.
[0146] Example 5 of the present invention
[0147] A copolymer of sodium acrylate (75 mol %) and hydroxypropyl acrylate (25 mol %) prepared by the process according to the present invention.
[0148] Preparation of monomer solution:
[0149] 660 g of tap water and 230 g of a 50 wt.% aqueous NaOH solution were placed in a 2 L reaction vessel with a cooling jacket. A dropping funnel with 270 g of acrylic acid was connected to the vessel and the acid was carefully dripped into the NaOH solution over 120 min. The temperature was kept below 25° C. Finally, 157.5 g of HPA was added and the monomer solution was purged with nitrogen.
[0150] Polymer Synthesis:
[0151] 500 g of water was placed in a 2 L reaction vessel equipped with a dropping funnel, stainless steel stirrer, pH controller and thermometer. The liquid was heated to 55°C under nitrogen purge and stirring. At this temperature, 0.6 g of Wako V50 dissolved in 5 g of water and 2.5 g of sodium peroxodisulfate dissolved in 5 g of water were added. Next, the monomer solution was added via a dropping funnel over 90 min, keeping the temperature raised to a maximum of 65°C. The reaction mixture was stirred at 60°C for an additional 60 min.
[0152] The final polymer solution had a viscosity of 152 000 mPas (20° C.) and a solids content of 24.1 wt. %. The pH was measured to be 4.9.
[0153] The solution was dried using a laboratory drum dryer (Merto Drum L, manufacturer Deutsche Vakuum Apparate, Holland Merten GmbH) at a temperature of 170° C. and a rotation speed of 1 rpm. The viscosity of a 5 wt.% aqueous solution of the resulting powder was determined to be 600 mPas. Residual acrylic acid was determined by HPLC to be 0.1 wt.%, and residual HPA to be 0.01 wt.%. The molecular weight (M) was measured by GPC. w ) was 1,097,000 Da. The insoluble content was determined to be <2 wt.%.
[0154] Example 6 of the present invention
[0155] A copolymer of sodium acrylate (79.5 mol %) and hydroxypropyl acrylate (20.5 mol %) prepared by the process according to the invention.
[0156] The synthetic route was modified in this example. Instead of preparing a combined monomer solution, acrylic acid, HPA and NaOH solutions were charged separately to the reactor. Small amounts of sodium acrylate and HPA were initially already present in the reactor (30 wt. % relative to the total amount of monomers).
[0157] 4400g of water is placed in a 10L reaction vessel equipped with a cooling jacket, a stainless steel agitator, a pH controller and a thermometer. Start the agitator, and load 340g of 50wt.% of NaOH aqueous solution, 324g of acrylic acid and 152g of HPA into the reactor. Under nitrogen purging and further stirring, the liquid is heated to 54°C. At this temperature, 2.4g of azo initiator 2,2'-azobis[2-methylpropionamidine] dihydrochloride (Wako V50) dissolved in 50g of water and 10g of sodium peroxodisulfate dissolved in 50g of water are added. Exothermic reaction is observed and cooling is started. In order to support cooling, 400g of cold water is also added.
[0158] Next, the addition of 756 g of acrylic acid and 353 g of HPA was started. The two monomers were metered in at a rate of 750 g / h and 450 g / h, respectively, by a peristaltic pump. When a temperature of 67° C. and a pH of 4.5 were reached, 800 g of 30 wt.% NaOH were added at a flow rate of 750 g / h to keep the pH at about 4.5. In order to keep the maximum temperature below 70° C., additional portions of a total of 700 g of cold water were added during the polymerization. After 70 min, the metering of the monomers was complete.
[0159] The final polymer solution had a viscosity of 30 000 mPas (20° C.) and a solids content of 22 wt.%. The pH was measured to be 4.5.
[0160] The solution was dried using a laboratory drum dryer (Merto Drum L, manufacturer Deutsche Vakuum Apparate, Holland Merten GmbH) at a temperature of 170° C. and a rotation speed of 1 rpm. The viscosity of a 5 wt.% aqueous solution of the resulting powder was determined to be 300 mPas. Residual acrylic acid was determined by HPLC to be 0.08 wt.%, and residual HPA to be 0 wt.%. The molecular weight (M) was measured by GPC. w ) was 944,000 Da. The insoluble content was determined to be <2 wt.%.
[0161] Comparative Example 3
[0162] Copolymer of sodium acrylate (79.5 mol%) and hydroxypropyl acrylate (20.5 mol%).
[0163] For comparative purposes, the product was not dried but the copolymer was tested as is.
[0164] 1000g of water was placed in a 2L reaction vessel equipped with a cooling jacket, a stainless steel agitator, a pH controller and a thermometer. The agitator was started and the liquid was heated to 58°C under a nitrogen purge. At this temperature, 0.6g of azo initiator 2,2'-azobis[2-methylpropionamidine] dihydrochloride (Wako V50) dissolved in 10g of water and 2.5g of sodium peroxodisulfate dissolved in 10g of water were added. Immediately, 270g of acrylic acid, 126.2g of HPA and 460g of 25wt.% of NaOH were added. All components were metered in at a rate of 185g / h, 100g / h, and 350-400g / h by a peristaltic pump, respectively. The amount of NaOH added was adjusted to keep the pH between 5-5.5. After 80min, the monomer metering was completed.
[0165] The final polymer solution had a viscosity of 124 000 mPas (20° C.) and a solids content of 24.4 wt.%. The pH was measured to be 5.5. The viscosity of the 5 wt.% aqueous solution was measured to be 320 mPas. Residual acrylic acid was determined by HPLC to be 0.13 wt.%, and residual HPA to be 0 wt.%. The molecular weight (M) was measured by GPC. w ) is 1,200,000Da.
[0166] Example 7 of the present invention
[0167] A copolymer of sodium acrylate (79.5 mol %) and hydroxypropyl acrylate (20.5 mol %) prepared by the process according to the invention.
[0168] 4200 g of water was placed in a 10 L reaction vessel equipped with a cooling jacket, a stainless steel stirrer, a pH controller and a thermometer. The stirrer was started and 105 g of a 50 wt.% aqueous NaOH solution, 108 g of acrylic acid and 50 g of HPA were charged into the reactor.
[0169] Under nitrogen purging and further stirring, the liquid was heated to 56°C. At this temperature, 2.4 g of azo initiator 2,2'-azobis[2-methylpropionamidine] dihydrochloride (Wako V50) dissolved in 50 g of water and 10 g of sodium peroxodisulfate dissolved in 50 g of water were added. An exothermic reaction was observed and cooling was initiated. Next, 970 g of acrylic acid, 445 g of HPA and 1380 g of 30 wt.% NaOH were added. These components were metered in at a rate of 800 g / h, 600 g / h and 1200 g / h, respectively, by a peristaltic pump. The amount of NaOH added was adjusted to keep the pH between 5–5.5. During the polymerization, a maximum temperature of 73°C was reached. After 70 min, the monomer metering was completed.
[0170] The final polymer solution had a viscosity of 10 000 mPas (20° C.) and a solids content of 25 wt.%. The pH was measured to be 5.2.
[0171] The solution was dried using a laboratory drum dryer (Merto Drum L, manufacturer Deutsche Vakuum Apparate, Holland Merten GmbH) at a temperature of 170° C. and a rotation speed of 1 rpm. The viscosity of a 5 wt.% aqueous solution of the resulting powder was determined to be 90 mPas. Residual acrylic acid was determined by HPLC to be 0.08 wt.%, and residual HPA to be 0.007 wt.%. The molecular weight (M) was measured by GPC. w ) was 663,000 Da. The insoluble content was determined to be <1 wt.%.
[0172] Example 8 of the present invention
[0173] A copolymer of sodium acrylate (79.5 mol %) and hydroxypropyl acrylate (20.5 mol %) prepared by the process according to the invention.
[0174] 3300 g of water were placed in a 10 L reaction vessel equipped with a cooling jacket, a stainless steel stirrer, a pH controller and a thermometer. The stirrer was started and 258 g of a 50 wt.% aqueous NaOH solution, 233 g of acrylic acid and 109 g of HPA were charged to the reactor. The liquid was heated to 55 °C under nitrogen purging and further stirring. At this temperature, 1.7 g of Wako V50 dissolved in 20 g of water and 7.2 g of sodium peroxodisulfate dissolved in 20 g of water were added. An exothermic reaction was observed and cooling was started. Next, the addition of 544 g of acrylic acid, 254 g of HPA and 400 g of 50 wt.% NaOH was started. These components were metered in at a rate of 550 g / h, 250 g / h and 550 g / h, respectively, by a peristaltic pump. The amount of NaOH added was adjusted to keep the pH between 4.5–5.0. During the polymerization, a maximum temperature of 69 °C was reached. After 60 min, the monomer metering was complete.
[0175] The final polymer solution had a viscosity of 80 000 mPas (20° C.) and a solids content of 25 wt.%. The pH was measured to be 4.6.
[0176] The solution was dried using a laboratory drum dryer (Merto Drum L, manufacturer Deutsche Vakuum Apparate, Holland Merten GmbH) at a temperature of 170° C. and a rotation speed of 1 rpm. The viscosity of a 5 wt.% aqueous solution of the resulting powder was determined to be 350 mPas. Residual acrylic acid was determined by HPLC to be 0.12 wt.%, and residual HPA to be 0 wt.%. The molecular weight (M) was measured by GPC. w ) was 1,141,000 Da. The insoluble content was determined to be <1 wt.%.
[0177] Example 9 of the present invention
[0178] A copolymer of sodium acrylate (79.5 mol %) and hydroxypropyl acrylate (20.5 mol %) prepared by the process according to the invention.
[0179] In this example, a different initiator package was used. 2,2'-[azobis(1-methylethylidene)]bis[4,5-dihydro-1H-imidazole dihydrochloride (10 h t1 / 2 temperature in water 44°C; Wako VA-044) was used instead of 2,2'-azobis[2-methylpropionamidine] dihydrochloride (10 h t1 / 2 temperature in water 56°C, Wako V50) + sodium peroxodisulfate.
[0180] 1700 g of water was placed in a 4 L reaction vessel equipped with a cooling jacket, a stainless steel stirrer, a pH controller and a thermometer. The stirrer was started, and 128 g of a 50 wt.% aqueous NaOH solution, 116 g of acrylic acid and 55 g of HPA were charged into the reactor. The liquid was heated to 57°C under nitrogen purge and further stirring.
[0181] At this temperature, 3 g of azo initiator 2,2'-azobis[2-methylpropionamidine] dihydrochloride ( V50). An exothermic reaction was observed and cooling was initiated. Next, the addition of 272 g of acrylic acid and 127 g of HPA was started. These components were metered in via peristaltic pumps at a rate of 230 g / h and 120 g / h, respectively. During the polymerization, a maximum temperature of 72.5 °C was reached. After 60 min, the metering of the monomers was complete.
[0182] The final polymer solution had a viscosity of 100 000 mPas (20° C.) and a solids content of 24.5 wt.%. The pH was measured to be 4.2. The viscosity of the 5 wt.% aqueous solution was measured to be 180 mPas. Residual acrylic acid was determined by HPLC to be 0.21 wt.%, and residual HPA to be 0 wt.%. Molecular weight (M) was measured by GPC. w ) is 1,000,000Da.
[0183] Example 10 of the present invention
[0184] A copolymer of sodium acrylate (79.5 mol %) and hydroxypropyl acrylate (20.5 mol %) prepared by the process according to the invention.
[0185] 4400 g of water was placed in a 10 L reaction vessel equipped with a cooling jacket, a stainless steel stirrer, a pH controller and a thermometer. The stirrer was started and 320 g of a 50 wt.% aqueous NaOH solution, 290 g of acrylic acid and 137.5 g of HPA were charged into the reactor. The liquid was heated to 49° C. under nitrogen purge and further stirring.
[0186] At this temperature, 3 g of Wako VA-044 dissolved in 50 g of water are added. An exothermic reaction is observed and cooling is initiated. Next, 680 g of acrylic acid and 318 g of HPA are added. These components are metered in via peristaltic pumps at a rate of 700 g / h and 300 g / h, respectively. During the polymerization, a maximum temperature of 77° C. is reached. After 64 min, the metering of the monomers is complete. The pH is adjusted to 6.3 with 200 g of a 25 wt.% aqueous NaOH solution.
[0187] The final polymer solution had a viscosity of 82 000 mPas (20° C.) and a solids content of 23.3 wt. %.
[0188] The solution was dried using a laboratory drum dryer (Merto Drum L, manufacturer Deutsche Vakuum Apparate, Holland Merten GmbH) at a temperature of 170° C. and a rotation speed of 1 rpm. The viscosity of a 5 wt.% aqueous solution of the resulting powder was determined to be 990 mPas. Residual acrylic acid was determined by HPLC to be 0.08 wt.%, and residual HPA to be 0 wt.%. The molecular weight (M) was measured by GPC. w ) was 1,218,000 Da. The insoluble content was determined to be <1 wt.%.
[0189] Example 11 of the present invention
[0190] A copolymer of sodium acrylate (79.5 mol %) and hydroxypropyl acrylate (20.5 mol %) prepared by the process according to the invention.
[0191] 1600 g of water was placed in a 4 L reaction vessel equipped with a cooling jacket, a stainless steel stirrer, a pH controller and a thermometer. The stirrer was started and 107 g of a 50 wt.% aqueous NaOH solution, 97 g of acrylic acid and 46 g of HPA were charged into the reactor. The liquid was heated to 49° C. under nitrogen purge and further stirring.
[0192] At this temperature, 2 g of Wako VA-044 dissolved in 20 g of water were added. An exothermic reaction was observed and cooling was initiated. Next, the addition of 227 g of acrylic acid, 106 g of HPA and 100 g of 50 wt.% NaOH was started. These components were metered in via a peristaltic pump at a rate of 230 g / h, 100 g / h and 100 g / h, respectively. The amount of NaOH added was adjusted to keep the pH between 5.0–5.5. During the polymerization, a maximum temperature of 62.5 °C was reached. After 70 min, the metering of the monomers was completed.
[0193] The final polymer solution had a viscosity of 39 000 mPas (20° C.) and a solids content of 22.6 wt. %. The pH was measured to be 4.9.
[0194] The solution was dried using a laboratory drum dryer (Merto Drum L, manufacturer Deutsche Vakuum Apparate, Holland Merten GmbH) at a temperature of 170° C. and a rotation speed of 1 rpm. The viscosity of a 5 wt.% aqueous solution of the resulting powder was determined to be 1500 mPas. Residual acrylic acid was determined by HPLC to be 0.08 wt.%, and residual HPA to be 0 wt.%. The molecular weight (M) was measured by GPC. w ) is 1,176,000Da.
[0195] Example 12 of the present invention
[0196] A copolymer of sodium acrylate (79.5 mol %) and hydroxypropyl acrylate (20.5 mol %) prepared by the process according to the invention.
[0197] 1600 g of water was placed in a 4 L reaction vessel equipped with a cooling jacket, a stainless steel stirrer, a pH controller and a thermometer. The stirrer was started and 107 g of a 50 wt.% aqueous NaOH solution, 97 g of acrylic acid and 46 g of HPA were charged to the reactor. The liquid was heated to 49 °C under nitrogen purge and further stirring. At this temperature, 2 g of Wako VA-044 dissolved in 20 g of water was added. An exothermic reaction was observed and cooling was started. Next, 227 g of acrylic acid, 106 g of HPA and 150 g of 50 wt.% of NaOH were started. These components were metered in at a rate of 230 g / h, 100 g / h and 100 g / h respectively by a peristaltic pump. The amount of NaOH added was adjusted to keep the pH between 5.0–5.5. During the polymerization, a maximum temperature of 66 °C was reached. After 70 min, the monomer metering was completed.
[0198] The final polymer solution had a viscosity of 44 000 mPas (20° C.) and a solids content of 23.1 wt. %. The pH was measured to be 5.3.
[0199] The solution was dried using a laboratory drum dryer (Merto Drum L, manufacturer Deutsche Vakuum Apparate, Holland Merten GmbH) at a temperature of 170° C. and a rotation speed of 1 rpm. The viscosity of a 5 wt.% aqueous solution of the resulting powder was determined to be 400 mPas. Residual acrylic acid was determined by HPLC to be 0.07 wt.%, and residual HPA to be 0 wt.%. The molecular weight (M) was measured by GPC. w ) is 1,049,000Da.
[0200] Example 13 of the present invention
[0201] A copolymer of sodium acrylate (79.5 mol %) and hydroxypropyl acrylate (20.5 mol %) prepared by the process according to the invention.
[0202] 1600 g of water was placed in a 4 L reaction vessel equipped with a cooling jacket, a stainless steel agitator, a pH controller and a thermometer. The agitator was started and 107 g of a 50 wt.% aqueous NaOH solution, 97 g of acrylic acid and 46 g of HPA were loaded into the reactor. The liquid was heated to 49°C under nitrogen purge and further stirring. At this temperature, 2 g of Wako VA-044 dissolved in 20 g of water was added. An exothermic reaction was observed and cooling was started. Next, 227 g of acrylic acid, 106 g of HPA and 200 g of 50 wt.% of NaOH were added. These components were metered in at a rate of 230 g / h, 100 g / h and 100 g / h, respectively, by a peristaltic pump. The amount of NaOH added was adjusted to keep the pH between 5.0 and 5.5. During the polymerization, a maximum temperature of 66°C was reached. After 70 min, the monomer metering was completed.
[0203] The final polymer solution had a viscosity of 24 000 mPas (20° C.) and a solids content of 23.0 wt. %. The pH was measured to be 5.7.
[0204] The solution was dried using a laboratory drum dryer (Merto Drum L, manufacturer Deutsche Vakuum Apparate, Holland Merten GmbH) at a temperature of 170° C. and a rotation speed of 1 rpm. The viscosity of a 5 wt.% aqueous solution of the resulting powder was determined to be 300 mPas. Residual acrylic acid was determined by HPLC to be 0.1 wt.%, and residual HPA to be 0 wt.%. The molecular weight (M) was measured by GPC. w ) is 950,000Da.
[0205] Example 14 of the present invention
[0206] A copolymer of sodium acrylate (79.5 mol %) and hydroxypropyl acrylate (20.5 mol %) prepared by the process according to the invention.
[0207] 4200 g of water was placed in a 10 L reaction vessel equipped with a cooling jacket, a stainless steel agitator, a pH controller and a thermometer. The agitator was started and 320 g of a 50 wt.% aqueous NaOH solution, 290 g of acrylic acid and 137.5 g of HPA were loaded into the reactor. The liquid was heated to 49° C. under nitrogen purge and further stirring. At this temperature, 3.6 g of Wako VA-044 dissolved in 50 g of water was added. An exothermic reaction was observed and cooling was started. Next, 680 g of acrylic acid, 318 g of HPA and 450 g of 50 wt.% of NaOH were added. These components were metered in at a rate of 700 g / h, 300 g / h and 450 g / h, respectively, by a peristaltic pump. The amount of NaOH added was adjusted to keep the pH between 4.5 and 5.5. During the polymerization, a maximum temperature of 82° C. was reached. After 64 min, the monomer metering was completed.
[0208] The final polymer solution had a viscosity of 16 800 mPas (20° C.) and a solids content of 25 wt.%. The pH was measured to be 6.1.
[0209] The solution was dried using a laboratory drum dryer (Merto Drum L, manufacturer Deutsche Vakuum Apparate, Holland Merten GmbH) at a temperature of 170° C. and a rotation speed of 1 rpm. The viscosity of a 5 wt.% aqueous solution of the resulting powder was determined to be 260 mPas. Residual acrylic acid was determined by HPLC to be 0.34 wt.%, and residual HPA to be 0 wt.%. The molecular weight (M) was measured by GPC. w ) was 878,000 Da. The insoluble content was determined to be <1 wt.%.
[0210] Example 15 of the present invention
[0211] A copolymer of sodium acrylate (79.5 mol %) and hydroxypropyl acrylate (20.5 mol %) prepared by the process according to the invention.
[0212] 4200 g of water was placed in a 10 L reaction vessel equipped with a cooling jacket, a stainless steel agitator, a pH controller and a thermometer. The agitator was started and 320 g of a 50 wt.% aqueous NaOH solution, 290 g of acrylic acid and 137.5 g of HPA were loaded into the reactor. The liquid was heated to 49°C under nitrogen purge and further stirring. At this temperature, 2.9 g of Wako VA-044 dissolved in 50 g of water was added. An exothermic reaction was observed and cooling was started. Next, 680 g of acrylic acid, 318 g of HPA and 400 g of 50 wt.% of NaOH were added. These components were metered in at a rate of 700 g / h, 300 g / h and 450 g / h, respectively, by a peristaltic pump. The amount of NaOH added was adjusted to keep the pH between 4.5 and 5.5. During the polymerization, a maximum temperature of 82°C was reached. After 68 min, the monomer metering was completed.
[0213] The final polymer solution had a viscosity of 55 000 mPas (20° C.) and a solids content of 25 wt.%. The pH was measured to be 5.7.
[0214] The solution was dried using a laboratory drum dryer (Merto Drum L, manufacturer Deutsche Vakuum Apparate, Holland Merten GmbH) at a temperature of 170° C. and a rotation speed of 1 rpm. The viscosity of a 5 wt.% aqueous solution of the resulting powder was determined to be 600 mPas. Residual acrylic acid was determined by HPLC to be 0.34 wt.%, and residual HPA to be 0 wt.%. The molecular weight (M) was measured by GPC. w ) was 851,000 Da. The insoluble content was determined to be <1 wt.%.
[0215] Example 16 of the present invention
[0216] A copolymer of sodium acrylate (79.5 mol %) and hydroxypropyl acrylate (20.5 mol %) prepared by the process according to the invention.
[0217] 4200 g of water was placed in a 10 L reaction vessel equipped with a cooling jacket, a stainless steel agitator, a pH controller and a thermometer. The agitator was started and 320 g of a 50 wt.% aqueous NaOH solution, 290 g of acrylic acid and 137.5 g of HPA were loaded into the reactor. The liquid was heated to 49°C under nitrogen purge and further stirring. At this temperature, 2.9 g of Wako VA-044 dissolved in 50 g of water was added. An exothermic reaction was observed and cooling was started. Next, 680 g of acrylic acid, 318 g of HPA and 450 g of 50 wt.% of NaOH were added. These components were metered in at a rate of 600 g / h, 300 g / h and 450 g / h, respectively, by a peristaltic pump. The amount of NaOH added was adjusted to keep the pH between 4.5 and 6. During the polymerization, a maximum temperature of 79°C was reached. After 62 min, the monomer metering was completed.
[0218] The final polymer solution had a viscosity of 43 000 mPas (20° C.) and a solids content of 22.8 wt. %. The pH was measured to be 6.2.
[0219] The solution was dried with a laboratory drum dryer (Merto Drum L, manufacturer Deutsche Vakuum Apparate, Holland Merten GmbH) at a temperature of 170° C. and a rotation speed of 1 rpm. The viscosity of a 5 wt.% aqueous solution of the resulting powder was measured to be 490 mPas. Residual acrylic acid was determined by HPLC to be 0.36 wt.%, and residual HPA to be 0 wt.%. The molecular weight (Mw) measured by GPC was 1,263,000 Da. The insoluble content was determined to be <1 wt.%.
[0220] Example 17 of the present invention
[0221] A copolymer of sodium acrylate (79.5 mol %) and hydroxypropyl acrylate (20.5 mol %) prepared by the process according to the invention.
[0222] At the end of the reaction, additional initiator is added in order to reduce the amount of residual monomers.
[0223] 4200 g of water was placed in a 10 L reaction vessel equipped with a cooling jacket, a stainless steel agitator, a pH controller and a thermometer. The agitator was started and 320 g of a 50 wt.% aqueous NaOH solution, 290 g of acrylic acid and 137.5 g of HPA were loaded into the reactor. The liquid was heated to 49°C under nitrogen purge and further stirring. At this temperature, 2.9 g of Wako VA-044 dissolved in 50 g of water was added. An exothermic reaction was observed and cooling was started. Next, 680 g of acrylic acid, 318 g of HPA and 450 g of 50 wt.% of NaOH were added. These components were metered in at a rate of 600 g / h, 300 g / h and 450 g / h, respectively, by a peristaltic pump. The amount of NaOH added was adjusted to keep the pH between 4.5 and 6. During the polymerization, a maximum temperature of 79°C was reached. After 62 min, the monomer metering was completed. After further stirring for 30 min, 0.5 g of Wako VA-044 dissolved in 50 g of water was added to reduce the residual monomer content.
[0224] The final polymer solution had a viscosity of 52 000 mPas (20° C.) and a solids content of 22.8 wt. %. The pH was measured to be 6.2.
[0225] The solution was dried with a laboratory drum dryer (Merto Drum L, manufacturer Deutsche Vakuum Apparate, Holland Merten GmbH) at a temperature of 170° C. and a rotation speed of 1 rpm. The viscosity of a 5 wt.% aqueous solution of the resulting powder was measured to be 690 mPas. Residual acrylic acid was determined by HPLC to be 0.22 wt.%, and residual HPA to be 0 wt.%. The molecular weight (Mw) measured by GPC was 1,295,000 Da. The insoluble content was determined to be <1 wt.%.
[0226] Example 18 of the present invention
[0227] A copolymer of sodium acrylate (79.5 mol %) and hydroxypropyl acrylate (20.5 mol %) prepared by the process according to the invention.
[0228] 4200 g of water was placed in a 10 L reaction vessel equipped with a cooling jacket, a stainless steel agitator, a pH controller and a thermometer. The agitator was started and 320 g of a 50 wt.% aqueous NaOH solution, 290 g of acrylic acid and 137.5 g of HPA were loaded into the reactor. The liquid was heated to 49°C under nitrogen purge and further stirring. At this temperature, 3.3 g of Wako VA-044 dissolved in 50 g of water was added. An exothermic reaction was observed and cooling was started. Next, 680 g of acrylic acid, 318 g of HPA and 450 g of 50 wt.% of NaOH were added. These components were metered in at a rate of 600 g / h, 300 g / h and 450 g / h, respectively, by a peristaltic pump. The amount of NaOH added was adjusted to keep the pH between 4.5 and 6. During the polymerization, a maximum temperature of 83°C was reached. After 67 min, the monomer metering was completed.
[0229] The final polymer solution had a viscosity of 14 000 mPas (20° C.) and a solids content of 23.5 wt. %. The pH was measured to be 6.2.
[0230] The solution was dried using a laboratory drum dryer (Merto Drum L, manufacturer Deutsche Vakuum Apparate, Holland Merten GmbH) at a temperature of 170° C. and a rotation speed of 1 rpm. The viscosity of a 5 wt.% aqueous solution of the resulting powder was determined to be 290 mPas. Residual acrylic acid was determined by HPLC to be 0.37 wt.%, and residual HPA to be 0 wt.%. The molecular weight (M) was measured by GPC. w ) was 1,101,000 Da. The insoluble content was determined to be <1 wt.%.
[0231] Example 19 of the present invention
[0232] A copolymer of sodium acrylate (79.5 mol %) and hydroxypropyl acrylate (20.5 mol %) prepared by the process according to the invention.
[0233] At the end of the reaction, additional initiator is added in order to reduce the amount of residual monomers.
[0234] 4200 g of water was placed in a 10 L reaction vessel equipped with a cooling jacket, a stainless steel agitator, a pH controller and a thermometer. The agitator was started and 320 g of a 50 wt.% aqueous NaOH solution, 290 g of acrylic acid and 137.5 g of HPA were loaded into the reactor. The liquid was heated to 49°C under nitrogen purge and further stirring. At this temperature, 3.3 g of Wako VA-044 dissolved in 50 g of water was added. An exothermic reaction was observed and cooling was started. Next, 680 g of acrylic acid, 318 g of HPA and 450 g of 50 wt.% of NaOH were added. These components were metered in at a rate of 600 g / h, 300 g / h and 450 g / h, respectively, by a peristaltic pump. The amount of NaOH added was adjusted to keep the pH between 4.5 and 6. During the polymerization, a maximum temperature of 83°C was reached. After 67 min, the monomer metering was completed. After further stirring for 30 min, 0.5 g of Wako VA-044 dissolved in 50 g of water was added to reduce the residual monomer content.
[0235] The final polymer solution had a viscosity of 18 000 mPas (20° C.) and a solids content of 23.5 wt. %. The pH was measured to be 6.2.
[0236] The solution was dried using a laboratory drum dryer (Merto Drum L, manufacturer Deutsche Vakuum Apparate, Holland Merten GmbH) at a temperature of 170° C. and a rotation speed of 1 rpm. The viscosity of a 5 wt.% aqueous solution of the resulting powder was determined to be 370 mPas. Residual acrylic acid was determined by HPLC to be 0.19 wt.%, and residual HPA to be 0 wt.%. The molecular weight (M) was measured by GPC. w ) was 1,086,000 Da. The insoluble content was determined to be <1 wt.%.
[0237] Application Testing
[0238] Decentralized testing
[0239] Shale inhibition is achieved by adding certain additives to the drilling fluid that prevent the clay or shale from absorbing water (i.e., swelling) and providing integrity to the cuttings.
[0240] The level of inhibition of different drilling fluid additives and formulations on shale is often evaluated through tests such as cuttings dispersion. A good indication of the inhibitory performance of an additive can be obtained by modifying the standard oilfield cuttings dispersion test based on API RP 13I Section 23: Shale Particle Disintegration Test by Hot Rolling. This test is used to screen the effectiveness of inhibitor additives to maintain the integrity of the cuttings and minimize the interaction of the fluid with the shale zone during drilling and completion operations.
[0241] Test principle:
[0242] A known weight of shale cuttings (size 2 to 5 mm, about 25 g) is added to a measured volume of the aqueous liquid to be tested (about 175 ml) in a container. The container is rotated (hot rolled at 93°C for about 16 hours) so that the cuttings are constantly stirred in the liquid; if the cuttings soften due to interaction with the test liquid, this will promote the decomposition and dispersion of the cuttings. After 16 hours of hot rolling, the container is cooled to room temperature, and the liquid containing the cuttings is poured onto a 0.5 mm sieve, the residual shale pieces are recovered, and washed with a 4 wt.% KCl aqueous solution and dried at 110°C for 3.5 hours. Afterwards, the sample is reweighed to determine the percentage of recovered shale. The remaining part becomes dispersed and passes through the sieve. The recovered weight is expressed as a percentage of the original weight added to the test liquid. The more inhibitory the test liquid is, the lower the degree of dispersion of the cuttings, and therefore the higher the amount of shale cuttings recovered.
[0243] Detailed procedures:
[0244] The basis of aqueous drilling fluids is typically a suspension of finely dispersed bentonite in water. Thus, as starting material for the drilling fluids to be tested, an aqueous suspension of bentonite (10 wt. %) was prepared.
[0245] Preparation of a suspension containing 10 wt.% bentonite:
[0246] 1. Add 450g of deionized water into a 1L plastic bottle,
[0247] 2. Stir the water with an overhead mixer,
[0248] 3. 50g of untreated sodium montmorillonite clay ( Premium NT) was added to water and stirred for at least 1 h, and
[0249] 4. After stirring with an overhead mixer, the bottle was closed and shaken vigorously (to remove clumps).
[0250] Preparation of drilling fluid:
[0251] 1. Add 50 g of bentonite suspension (10 wt.% bentonite) into the cup of Hamilton beach mixer,
[0252] 2. Add 305g of deionized water to the Hamilton beach mixer and stir at "low speed" for 5 minutes.
[0253] 3. Add 15g KCl to the Hamilton beach mixer and stir for 5 minutes.
[0254] 4. Add 2 g of shale encapsulant and stir for 20 min (if lumps still exist, stir for another 20-40 min). The 2 g amount is related to the solid shale inhibitor; if the shale inhibitor is a solution or dispersion, the amount of 305 g of water is reduced accordingly to ensure the same polymer content in all experiments (0.5 wt.% relative to the total amount of all components of the drilling fluid),
[0255] 5. Divide the drilling fluid into 2 portions and add each portion to a 250ml glass bottle.
[0256] 6. Add 25 g of bentonite cuttings (2 to 5 mm in size) to each bottle, close the bottle and shake quickly to coat all the cuttings with drilling fluid,
[0257] 7. The mixture was aged at 93.3°C for 16 h, and
[0258] 8. The slurry was cooled after aging in the water bath and then subjected to sieve testing.
[0259] Screening test
[0260] 1.500μm sieve weighs the seeds when dry,
[0261] 2. Pour the aged drilling fluid containing cuttings through the sieve and wash the cuttings with 4wt.% KCl solution until the washing solution becomes clear after flowing through the sieve with cuttings.
[0262] 3. Dry the sieve with a paper towel and weigh the wet cuttings.
[0263] 4. Dry the cuttings in a sieve at 110°C until a constant mass is measured (3.5 h is sufficient),
[0264] 5. Shale recovery rate in %, and
[0265] 6. Calculate the average shale recovery rate from the 2 tests.
[0266] Table 1 shows the results of the dispersion tests performed on the samples of each of the above examples.
[0267]
[0268]
Claims
1. A method for preparing a water-soluble polymer in powder form by free radical polymerization of at least two water-soluble monoethylenically unsaturated monomers (A) and (B), wherein Monomer (A) has the formula H2C=C(R 1 )-CO-XR 2 , where R 1 is H or CH3, X is O or NR 3 , where R 3 is H or CH3, and R 2 is a hydrocarbon radical containing at least one OH side group or having the formula –(CH2CH(R 4 )-O) n R 5 A group in which R 4 and R 5 are independently H or CH3, and n is selected from 1 to 20, and wherein the amount of monomer (A) is 0.1 to 30 mol% relative to the total amount of all monomers, and Monomer (B) is a monomer different from (A) and has the general formula H2C=C(R 1 )-R 6 , where R 1 has the meaning as defined above, and R 6 is a hydrophilic group, and wherein the amount of monomer (B) is 70 to 99.9 mol% relative to the total amount of all monomers, and It is characterized in that The method comprises at least the following steps i) adding an aqueous base fluid to a container, ii) adding at least one free radical initiator to the container and dissolving the free radical initiator in the aqueous base fluid, iii) continuously metering the monomers into the vessel, and iv) removing the obtained water-soluble polymer from the container and drying it, And wherein the maximum temperature of the vessel is equal to or less than 100°C at any point during the process.
2. The method according to claim 1, characterized in that In step iv), the polymer is dried using a drum dryer.
3. The method according to any one of the preceding claims, characterized in that An additional amount of at least one free radical initiator is added to the container after step iii).
4. The method according to any one of the preceding claims, characterized in that In iii), the monomers are metered continuously into the vessel over the course of 15-120 min, preferably 30-90 min, more preferably 45-75 min.
5. The method according to any one of the preceding claims, characterized in that These monomers in step iii) are added as a monomer mixture.
6. The method according to any one of the preceding claims, characterized in that The monomers in step iii) are added separately.
7. The method according to any one of the preceding claims, characterized in that After the metered addition of these monomers is complete, the reaction mixture obtained in step iii) is stirred at a temperature between 45 and 85° C., preferably between 55 and 85° C., more preferably between 55 and 70° C., for a further 30 min to 3 h.
8. The method according to any one of the preceding claims, characterized in that Between steps i) and ii), up to 30 wt. % of the monomers used in the process are added to the vessel, relative to the total amount of monomers added to the vessel during the process.
9. The method according to any one of the preceding claims, characterized in that The maximum temperature of the vessel is equal to or lower than 90°C, preferably equal to or lower than 85°C at any point during the process.
10. The method according to any one of the preceding claims, characterized in that The free radical initiator in water for 10 h 1 / 2 temperature is 20°C to 70°C, preferably 40°C to 60°C.
11. The method according to any one of the preceding claims, characterized in that The water-soluble polymer contains 5 to 25 mol %, preferably 15 to 25 mol %, of at least one monomer (A), relative to the total amount of all monomers.
12. The method according to any one of the preceding claims, characterized in that At least one monomer (B) is (meth)acrylic acid or a salt thereof.
13. The method according to claim 12, characterized in that The water-soluble polymer comprises 75-85 mol % of (meth)acrylic acid or a salt thereof and 15-25 mol % of a monomer (A).
14. The method according to any one of the preceding claims, characterized in that At least one monomer (A) is selected from hydroxyalkyl (meth)acrylates, hydroxyalkyl (meth)acrylamides and amino alcohol (meth)acrylates, wherein the term "alkyl" is a straight chain alkyl group containing 1 to 12 carbon atoms, preferably 1 to 6 carbon atoms, most preferably 1 to 4 carbon atoms.
15. The method according to claim 14, characterized in that At least one monomer (A) is hydroxypropyl (meth)acrylate.
16. The method according to any one of the preceding claims, characterized in that The final polymer concentration in the reaction vessel before step iv) is in the range of 18 to 35 wt.%, preferably in the range of 18 to 30 wt.%.
17. Use of a water-soluble polymer in the field of oil drilling, wherein the water-soluble polymer is in powder form and is obtainable by a process comprising free radical polymerization of at least two water-soluble monoethylenically unsaturated monomers (A) and (B), wherein Monomer (A) has the formula H2C=C(R 1 )-CO-XR 2 , where R 1 is H or CH3, X is O or NR 3 , where R 3 is H or CH3, and R 2 is a hydrocarbon radical containing at least one OH side group or having the formula –(CH2CH(R 4 )-O) n R 5 A group in which R 4 and R 5 are independently H or CH3, and n is selected from 1 to 20, and wherein the amount of monomer (A) is 0.1 to 30 mol% relative to the total amount of all monomers, and Monomer (B) is a monomer different from (A) and has the general formula H2C=C(R 1 )-R 6 , where R 1 has the meaning as defined above, and R 6 is a hydrophilic group, and wherein the amount of monomer (B) is 70 to 99.9 mol% relative to the total amount of all monomers, and It is characterized in that The method comprises at least the following steps i) adding an aqueous base fluid to a container, ii) adding at least one free radical initiator to the container and dissolving the free radical initiator in the aqueous base fluid, iii) continuously metering the monomers into the vessel, and iv) removing the obtained water-soluble polymer from the container and drying it, And wherein the maximum temperature of the vessel is equal to or less than 100°C at any point during the process.
18. The use according to claim 17, characterized in that The water-soluble polymers are used as shale encapsulants and / or shale inhibitors.
Citation Information
Patent Citations
Use of water-soluble polymers as adhesives
EP0344589A1
Water-soluble hydroxyalkyl polymer obtained by a method of inverse suspension or inverse emulsion polymerisation
EP3177654B1
Production of self-crosslinking water-absorbing resin
JP1981161413A
Curable aqueous composition
US20130289171A1
Water-soluble hydroxyalkyl polymer obtained by a method of inverse suspension or inverse emulsion polymerisation
US20170204210A1